Genotype x Environment Interactions in Buffel Grass - Roy, P K; Yadav, M S; Sudhakar, N (Annals of Arid Zone, 2025)
Green fodder and dry matter yields of ten buffel grass (Cenchrus ciliaris Linn.) varieties were recorded in nine environments (location - year combinations). Joint regression analysis revealed significant variation due to environnrents, genotypes and genotype x environment interaction for each yield. Growth response index and stability indices were used to conrpare the varieties for specific aptation and stability of forage production. None of the varieties combined high mean yield with average response and stability as desired in an ideal population. CAZRI 358, CAZRI 531, Dundel Anjan and CAZRI 1263 were stable in performance. Adaptation to low environment was found in CAZRI 358 and Bundel Anjan, whereas, CAZRI 1263 appeared to suits high environment. Considering the difficulties for recombination breeding in an apomictic species like buffel grass, population improvement through varietal mixtures is suggested.